On the identity of the tiger beetle Cicindela philippinensis Mandl, 1956 (Coleoptera: Carabidae: Cicindelinae) - Zettel, Herbert; Pangantihon, Clister V. (Zootaxa, 2015)
In the course of preparing a key to the Philippine tiger beetle genera (Pangantihon & Zettel, in prep.) it became necessary to examine the holotype of Cicindela philippinensis Mandl, 1956, the only specimen from the Philippines that has been tentatively assigned to the genus Myriochila Motschulsky, 1857.